Exploring the inclusion of women in work-life policy- and practice-making and its influence on career-advancement decisions at a state-owned entity - Nassar, Aneesa (Graduate School of Business (GSB), 2025)
This study explored the experiences and perceptions of women employees' work-life integration, inclusion in work-life policy- and practice-making, and its influence on their career-advancement choices at Transnet Port Terminals (TPT), an operating division of Transnet Ltd, a State-Owned Entity in South Africa. The main research question was: “What role does inclusion in work-life policy- and practice-making and subsequent work-life integration practices play for women employees when making career-advancement choices?” Vast literature is available on women in the workplace and work-life perceptions. However, there is little exploration of this topic within a State-Owned Entity setting, where women are affiliated to two distinctive groups, namely, the Bargaining Unit (trade unions with collective bargaining power) and Non-Bargaining Unit (management employees without collective bargaining power). The research was conducted using a multi-method qualitative approach. Semi-structured interviews were conducted with women employees and managers of women employees to identify the discourses that construct their perceptions of women's inclusion in work-life policy- and practice- making, work-life experiences, and their influence on career-advancement choices. Also, selected policies were analysed to understand how these policies shaped work life and employment equity at the organisation. Some of the key findings of the study include: - Due to collective bargaining and resultant employee related policies, women in the Non- Bargaining Unit did not receive some of the same work-life benefits that their Bargaining Unit colleagues enjoyed. This indicates a ‘union or collective bargaining gap' – where women in the same organisation who have the same needs receive different benefits due to their collective bargaining status. - Participants expressed their desire to be present and meet their responsibilities in both the work and life spheres. This suggests a new construct of perhaps “work-life satisfaction”. - Family-supportive managers was found to be a key positive influence in participants work-life satisfaction. The study concludes with a praxis model, identifying positive elements that are in place at the organisation and suggesting initiatives to build on these to create an inclusive environment where women employees can influence work-life policy- and practice-making and make positive career-advancement choices at the organisation.